Comparison of in-house immunofluorescence assay (IFA) and commercial enzyme-linked immunosorbent assay (ELISA) for Coxiella burnetii infection in cattle - França, Danilo Alves [UNESP]; Sampaio, Aryele Nunes da Cruz Encide [UNESP]; Possebon, Fábio Sossai [UNESP]; Reis Teixeira, Wanderson Sirley [UNESP]; Ribeiro, Bruna Letícia Devidé [UNESP]; Labruna, Marcelo Bahia; Costa, Francisco Borges; Sidi-Boumedine, Karim; Pereira, Juliano Gonçalves [UNESP]; Rousset, Élodie; Thiéry, Richard; Pereira dos Santos, Fabiana Cristina; et al. (Springer Nature, 2025)
Coxiellosis, often asymptomatic in animals, can cause significant reproductive losses and massive shedding of Coxiella burnetii during parturition. Serological surveillance is essential for identifying positive herds and implementing control measures to protect animal and human health. The World Organization for Animal Health (WOAH) recommends the enzyme-linked immunosorbent assay (ELISA) for animal serosurveys due to its high sensitivity and operational simplicity. However, in many countries, the absence of authorized commercial kits and the high cost of imports limit both epidemiological surveillance and clinical diagnosis. This study evaluated the diagnostic performance of an in-house immunofluorescence assay (IFA) compared with a commercial ELISA kit (IDVet ID Screen Q fever indirect multi-species). In a set of 182 bovine sera, the in-house IFA achieved a sensitivity of 84.78%, specificity of 98.89%, and diagnostic accuracy of 91.76%, with a Cohen’s kappa coefficient of 0.835 (95% CI: 0.692–0.979), indicating almost perfect agreement. The positive predictive value (PPV) was 98.73%, and the negative predictive value (NPV) was 86.41%. The moderate positive correlation between IFA titers and ELISA S/P% values (ρ = 0.503; p < 0.0001) supports their overall concordance despite differences in antigen origin. These results indicate that the in-house IFA is a reliable alternative for diagnosing and conducting epidemiological surveys of C. burnetii infection in cattle, particularly in settings where no commercial kit is available. Its high specificity and PPV make it especially valuable for confirming infection status in surveillance programs.